Conventional in vitro fertilization enhances preimplantation genetic testing for aneuploidy outcomes in couples with non-male factor infertility - Xiaolan Li; Qian Li; Yajie Chang; Shujing He; Yanfang Wang; Xiaoyan Liang; Zhiqiang Zhang (Scientific Reports)
Abstract While extensive research has compared ICSI and c-IVF in general ART outcomes, limited evidence exists regarding their relative efficacy and safety in PGT-A cycles. Therefore, we conducted a large retrospective cohort study to evaluate the effect of conventional in vitro fertilization (c-IVF) on the outcomes of preimplantation genetic testing for aneuploidy (PGT-A) in couples with non-male factor infertility. We conducted a large retrospective cohort study including 578 PGT-A cycles with c-IVF performed on couples with non-male factor infertility at our center between January 2019 and October 2024. To control for confounding factors, 578 PGT-A cycles with ICSI during the same period were selected as a control group. Matching was based on maternal age (± 2 years), number of oocytes retrieved (± 3), and progressive motile sperm count (± 3 × 106). The primary outcome was PGT-A results, while secondary outcomes included the 2PN fertilization rate, blastocyst available for biopsy per 2PN zygote and blastocyst available for biopsy per oocyte retrieved. Baseline characteristics, including parental age, AMH, antral follicle count (AFC), BMI, progressive motile sperm count, and PGT indications, were comparable between groups. Although the 2PN fertilization rate was significantly higher in the ICSI-PGT-A group (65.88% vs. 78.46%, P < 0.001), the 2 PN fertilization rate per retrieved oocyte (65.88% vs. 60.48%, P < 0.001), transferable embryo rate on day 3 (76.67% vs. 74.38%, P = 0.029), blastocyst formation rate per 2PN zygote (51.54% vs. 48.32%, P = 0.008), blastocyst available for biopsy per 2PN zygote (35.60% vs. 29.46%, P < 0.001), and blastocyst available for biopsy per oocyte retrieved (23.45% vs. 17.82%, P < 0.001) were significantly lower in the ICSI-PGT-A group. PGT-A results from 1,268 biopsy samples in the c-IVF group and 936 samples in the ICSI group revealed no significant differences in chromosomal euploidy, aneuploidy, mosaicism, or “No-call” rates. However, after controlling the potential confounders, c-IVF demonstrated significantly higher euploid embryo rate compared to ICSI (adjusted RR = 1.611, 95% CI 1.228–2.114, P = 0.001). Patterns of chromosomal aberrations were similar between groups, with chromosomes 15, 16, 21, and 22 showing the highest frequencies of abnormalities. Notably, no parental contamination was detected in the c-IVF group, while one case of maternal contamination was reported in the ICSI group. Our data suggested c-IVF could improve PGT-A outcomes in couples with non-male factor infertility and exhibited a low risk of parental contamination. c-IVF-PGT-A represents a safe, effective, and cost-efficient strategy for these couples.